First case report of an adrenocortical carcinoma caused by a BRCA2 mutation. Issue 36 (September 2016) - El Ghorayeb, Nada; Grunenwald, Solange; Nolet, Serge; Primeau, Vanessa; Côté, Stéphanie; Maugard, Christine M.; Lacroix, André; Gaboury, Louis; Bourdeau, Isabelle
Abstract: Background: Adrenocortical carcinoma (ACC) may rarely be a component of inherited cancer syndromes such as Li-Fraumeni syndrome and Beckwith-Wiedemann syndrome. ACC caused by a BRCA2 mutation has never been reported. Methods: Nucleotide sequencing of BRCA2 in lymphocyte and tumoral DNA of a 50-year-old male who presented with an androgen-secreting ACC and a strong family history of breast, ovarian, and pancreatic cancers. Results: A germline BRCA2 2 bp heterozygous deletion at nucleotide 8765 (8765delAG) leading to a frameshift mutation (p.Glu2846GlyfsX23) was detected. Only the BRCA2 deleted allele was retained in the ACC tumoral DNA compared with the control DNA supporting a loss of heterozygosity in the tumor. Conclusion: This is the first reported case of a patient with ACC associated with a BRCA2 germline mutation. Loss of heterozygosity in ACC DNA suggests a causal link with the BRCA2 8765delAG mutation.